COVID-19 vaccine candidates and vaccine development platforms available worldwide - Nilgun Duman; Zahraa ALzaidi; Busra Aynekin; Duygu Taskin; Busra Demirors; Abdulbaki Yildirim; Izem Olcay Sahin; Faik Bilgili; Eda Tahir Turanli; Tommaso Beccari; Matteo Bertelli; Munis Dundar (Elsevier, 2021)
The pandemic caused by the worldwide spread of the coronavirus, which first appeared in 2019, has been named coronavirus disease 19 (COVID-19). More than 4.5 million deaths have been recorded due to the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), according to the World Health Organization. COVID-19 Dashboard in September 2021. Apart from the wildtype, other variations have been successfully transmitted early in the outbreak although they were not discovered until March 2020. Modifications in the SARS-CoV-2 genetic material, such as mutation and recombination, have the ability to modify the viral life span, along with transitivity, cellular tropism, and symptom severity. Several processes are involved in introducing novel vaccines to the population, including vaccine manufacturing, preclinical studies, Food and Drug Administration permission or certification, processing, and marketing. COVID-19 vaccine candidates have been developed by a number of public and private groups employing a variety of strategies, such as RNA, DNA, protein, and viral vectored vaccines. This comprehensive review, which included the most subsequent evidence on unique features of SARS-CoV-2 and the associated morbidity and mortality, was carried out using a systematic search of recent online databases in order to generate useful knowledge about the COVID-19 updated versions and their consequences on the disease symptoms and vaccine development.